Enhancing Students’ Motivation and Creativity through the Socialization of Human Resource Planning Strategies to Foster an Entrepreneurial Spirit at SMKN 1 Ciruas - Darma Jata, Anak Agung Gede; Ghoni, Ahmad (Majalah Ilmiah UPI YPTK, 2025)
The objective of this Community Service Program (Pengabdian kepada Masyarakat/PKM) was carried out as an implementation of the Tri Dharma of Higher Education, particularly in the aspect of community engagement oriented toward empowering students within the school environment. The primary focus of the activity was to enhance motivation, creativity, and human resource (HR) planning skills among students of SMKN 1 Ciruas as an effort to foster an entrepreneurial spirit from an early age. This program was designed based on the students’ real needs, as they still faced low learning motivation, lack of self-confidence, and limited understanding of how to develop career plans and utilize their potential to face future challenges. The implementation methods employed expository and inquiry-based approaches. The expository method was used to deliver fundamental concepts of human resource planning, motivation, creativity, and basic principles of entrepreneurship. Meanwhile, the inquiry method encouraged students to think critically through group discussions, case studies, brainstorming business ideas, and simulations of career planning. The integration of these two methods enabled students to acquire theoretical knowledge while also gaining practical experience relevant to their personal development needs. The results of the program indicated an improvement in students’ understanding of the importance of individual-level human resource planning, including the ability to recognize personal potential, set short-term and long-term goals, and design career development strategies. Students’ learning motivation and interest in entrepreneurship also increased, as evidenced by their active participation in discussions and their confidence in expressing creative business ideas. In addition, students’ creativity developed through exercises in designing simple product or service concepts relevant to their surrounding environment. The impact of the program was not only felt by students individually but also by the school, as it contributed to the growth of an entrepreneurial culture and opened opportunities for continued collaboration between the school and higher education institutions. Overall, this PKM activity successfully made a tangible contribution to improving the quality of human resources at SMKN 1 Ciruas, particularly through strengthening motivation, creativity, self-planning skills, and entrepreneurial spirit. This program is expected to become a sustainable initiative that supports students’ readiness to enter the workforce or to start independent entrepreneurial ventures. Keywords: Motivation, Creativity, Human Resource Planning, Entrepreneurship, SMKN 1 Ciruas, Community Service Program.